PENDIDIKAN ANTI KORUPSI DALAM KACAMATA AGAMA HINDU - Ni Putu Rosita Dian Sari (Universitas Pendidikan Ganesha, 2023)
There is no end to the issue of corruption. There have been many strategic efforts designed by both the regional and central governments which oblige universities to carry out anti-corruption education (Kemenristekdikti Regulation Number 33 of 2019). Much research has been done on the implementation of corruption and corruption education at the formal education level, for this reason this discussion focuses on anti-corruption education in a religion, one of which is Hinduism. The research method used is to use library methods derived from journals and books as well as internet media. The results of the study show that in the perspective of Hinduism, corruption is considered an adharma act, which can have a negative impact not only on the perpetrator but on the wider community, nation and state. Then anti-corruption education in Hindu teachings is carried out by instilling values of integrity and character based on the Vedic Scriptures.